Zhang Zai's Cosmology of Qi/qi and the Refutation of Arrogant Anthropocentrism: Confucian Green Theory Illustrated. (1st October 2022) - Kassiola, Joel Jay
This essay seeks to demonstrate the following: 1. the value of metaphysical cosmology to our relationship with nature, and to making policy about the environment; 2. the mistaken nature and harmful consequences of the hegemonic cosmology of anthropocentrism; and, 3. the possibility of Zhang Zai's Qi/qi Great Harmony cosmology as both the refutation of and replacement for anthropocentrism. The essay concludes that ultimate moral progress of expanding the self from the narrow and exclusionary views of anthropocentrism consists in cosmocentrism, or the transformation of thought to a cosmological perspective as exemplified by Zhang Zai's Great Harmony continual cyclical process of Qi/qi. It is argued that positive metaphysical visions such as Zhang Zai's can negate anthropocentric cosmology and inspire us to view our relationship with the environment in a fundamentally enlightened and more respectful way, which is not arrogantly self-centred, disconnected and supremacist.